First person - Deepika Vasudevan (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Deepika Vasudevan is first author on ' A protein-trap allele reveals roles for Drosophila ATF4 in photoreceptor degeneration, oogenesis and wing development', published in DMM. Deepika conducted the research described in this article while a postdoctoral fellow in Hyung Don Ryoo's lab at New York University Grossman School of Medicine, New York, NY, USA, and is now an assistant professor at University of Pittsburgh School of Medicine, Pittsburgh, PA, USA, investigating cellular stress responses in disease and development.